A comprehensive molecular interaction map of the budding yeast cell cycle - Kazunari Kaizu; Samik Ghosh; Yukiko Matsuoka; Hisao Moriya; Yuki Shimizu‐Yoshida; Hiroaki Kitano (Molecular Systems Biology)
Abstract With the accumulation of data on complex molecular machineries coordinating cell‐cycle dynamics, coupled with its central function in disease patho‐physiologies, it is becoming increasingly important to collate the disparate knowledge sources into a comprehensive molecular network amenable to systems‐level analyses. In this work, we present a comprehensive map of the budding yeast cell‐cycle, curating reactions from ∼600 original papers. Toward leveraging the map as a framework to explore the underlying network architecture, we abstract the molecular components into three planes—signaling, cell‐cycle core and structural planes. The planar view together with topological analyses facilitates network‐centric identification of functions and control mechanisms. Further, we perform a comparative motif analysis to identify around 194 motifs including feed‐forward, mutual inhibitory and feedback mechanisms contributing to cell‐cycle robustness. We envisage the open access, comprehensive cell‐cycle map to open roads toward community‐based deeper understanding of cell‐cycle dynamics.